ANALYSIS OF THE LEVEL OF PHYSICAL FITNESS AND NUTRITION STATUS IN ATHLETES OF THE DKI PLATE ATHLETES OF HAND BALL SPORTS TOWARDS THE XX POND OF PAPUA 2021 IN THE PANDEMIC PERIOD - Muhammad Arif; Slamet Sukriadi (Journal of Physical Education and Sport Science, 2021)
Covid-19 in every country is increasing so that WHO recommends carrying out activities that cause crowds, so all sporting events are postponed or even cancelled. So that training for athletes is limited and not optimal, making it a new problem for athletes' physical fitness, besides the order to stay at home makes the athletes' nutrition not well controlled. This study aims to determine the analysis of the level of physical fitness and nutritional status in the athletes of the Sports Branch of Handball to Pon XX Papua 2021 in a Pandemic Period. This study uses a descriptive research technique method through a quantitative approach which emphasizes the assessment in the form of numbers for the phenomenon being observed. This study uses a total sampling technique with research subjects namely the 2021 athletes in the Handball sport. Based on the results of the data that has been obtained from the study, it shows that the level of physical fitness in the athletes of the DKI Jakarta handball Pelatda during the COVID-19 period in 2021 on average is very good, and has an average level of nutritional status in the normal or ideal category. category perfect as many as 1 athlete (7%) with very good category as many as 9 athletes (60%), and with good category as much as 5 athletes (33%).